Moderne School : maandblad voor opvoeding en onderwijs. (Brussel, 1932)
Bibliotheek E. Anseele
Hoofdredactie: J.E. Verheyen, Tervuerenlaan 55, Jubelpark, Brussel
Redactie: Louis Verniers, M. Depuydt, L. Vanderbeeken, R. Mariën
Beheer/Administratie: Tervuerenlaan 55, Jubelpark, Brussel
Nederlands
Periodiek